TERJEMAHAN ASPEK BUDAYA DALAM SUBTITLE FILM DATE NIGHT - Mursyid Kasmir Naserly (LPPM Universitas Bina Sarana Informatika, 2017)
Abstrak – The purpose of this study was to obtain a comprehensive picture of the cultural aspects in the movie Date Night subtitle translation. Translation is traced in terms of culture and translation. This study is a qualitative study using content analysis techniques. Object of this research is the translation subtitles on the movie Date Night, Shawn Levy's film which is in English and translated into Indonesian in the form of subtitling. The film highlights the social and cultural life in America, ranging from divorce, crime to political themes; it would not be surprised if this film had won several awards in 2010 and 2011. There are five aspects of the approach used in the research culture, including the ecological aspects, aspects of material culture, social cultural aspects, organizational aspects, customs, activities, concepts, beliefs and aspects of the habits and body language. Subtitle translation that has mixed with the cultural aspects of translation approaches and methods of translation strategies. The findings of this study as follows, aspects of culture found in the subtitle translation tends to refer to the translation of communicative strategies and make the target language as a direction for conveying information to readers. The key is the translator skills to establish an effective and concise language of the subtitle display. Key words: cultural aspects, subtitle translation, translation, film